Ocena sprawności fizycznej w aspekcie aktywności fizycznej kobiet po 60. roku życia = Fitness assesment in the aspect of physical activity of women over 60 years of age - Dziubek, Wioletta; Struck, Klaudia; Rogowski, Łukasz; Dąbrowska, Grażyna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of the article was fitness assessment in the aspect of physical activity of women over 60 years of age. The research included the group of 53 women. Group I (n = 32) comprised female students of the University of the Third Age and group II (n = 21) consisted of Senior Club members. A Fullteron test was used for fitness assessment, whereas to evaluate the level of physical activity the authors used a long form of International Physical Activity Questionnaire (IPAQ).
Keywords: physical activity; physical fitness; the elderly; Fullerton Test; Rikli & Jones test; 6 Minute Walk Test (6 MWT); International Physical Activity Questionnaires (IPAQ); aktywność fizyczna; sprawność fizyczna; osoby starsze